Effect of Physical Experience Towards Purchase Intention in Online-To-Offline Commerce Fabelio With Perceived Value and Perceived Risk as Mediator Variable - Sri Fatmayenti; Lenny Christina Nawangsari; Bambang Purwoko Kusumo Bintoro (Jurnal Scientia, 2024)
As Indonesian e-commerce companies start to implement O2O commerce by providing physical store or showroom, Fabelio is also one of the many. However, not many researches found on the effect of the physical experience as one of the characteristics of O2O commerce towards customer purchase intention in Indonesia, despite significant amount of capital spent by Fabelio to provide 20 showrooms in Jabodetabek and Bandung area to date. Hence, it is important for Fabelio to know if their showrooms providing physical experience will affect customers’ purchase intention, and know how to utilize their showrooms to attract more customers. The objective of this research is to find out the effect of physical experience towards purchase intention directly, or with perceived value and perceived risk as mediator variable. This research is a quantitative research, with data used in this study were obtained through a questionnaire given to 56 respondents. SEM PLS method was used to test the model and hypothesis. The result of this study indicates that physical experience affects perceived value and perceived risk directly, perceived value affects purchase intention directly, and physical experience affects purchase intention with perceived value as mediator variable.